2021
DOI: 10.1186/s12955-021-01669-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antipsychotics in children and adolescents with autism spectrum disorder: a systematic review and meta-analysis

Abstract: Background The net health benefit of using antipsychotics in children and adolescents with ASD is unclear. This review was performed to provide the evidence necessary to inform the Italian national guidelines for the management of ASD. Methods We performed a systematic review of randomized controlled trials (RCTs) comparing antipsychotics versus placebo for the treatment of ASD in children and adolescents. For efficacy, acceptability and safety we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 104 publications
3
45
0
Order By: Relevance
“…Pharmacological treatment options including antipsychotic agents and stimulant medications are often used to address the symptoms of ASD and co-occurring conditions [ 5 ] and are considered effective in alleviating stereotypies, irritability, and obsessions [ 6 ], yet a risk-benefit analysis of pharmacotherapy should be performed in each case [ 7 ]. On top of that, caregivers appear to have a hesitant attitude towards psychotropic medications [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological treatment options including antipsychotic agents and stimulant medications are often used to address the symptoms of ASD and co-occurring conditions [ 5 ] and are considered effective in alleviating stereotypies, irritability, and obsessions [ 6 ], yet a risk-benefit analysis of pharmacotherapy should be performed in each case [ 7 ]. On top of that, caregivers appear to have a hesitant attitude towards psychotropic medications [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many correlated medicinal interventions against the common symptoms in both diseases have been adopted. For example, for aggressive and agitated ASD and AD patients, antipsychotics, including quetiapine and risperidone, have been found effective [ 22 , 23 , 24 ]. For depression and anxiety, SSRIs (selective serotonin reuptake inhibitors), such as venlafaxine and citalopram, have been recommended [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, for aggressive and agitated ASD and AD patients, antipsychotics, including quetiapine and risperidone, have been found effective [ 22 , 23 , 24 ]. For depression and anxiety, SSRIs (selective serotonin reuptake inhibitors), such as venlafaxine and citalopram, have been recommended [ 24 , 25 , 26 ]. Furthermore, to manage sleep problems and improve neuron health and physiology, melatonin has been found effective [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is limited evidence that medications influence the core symptoms of ASD, such as social interaction and communication, and the presence of restricted behaviors, interests, and activities [7]. Rather, the medications are aimed at addressing associated behavioral symptoms, such as irritability, tantrums, aggression, self-harm, hyperactivity, and impulsivity.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, the medications are aimed at addressing associated behavioral symptoms, such as irritability, tantrums, aggression, self-harm, hyperactivity, and impulsivity. Recent reviews of well-conducted randomized control trials contrasting risperidone with placebos report improvements in irritability and tantrums with some reduction in aggressive episodes and self-injurious behaviors [7,8]. Likewise, methylphenidate (Ritalin) has been well studied with improvements noted in hyperactivity and impulsivity across multiple studies, but no benefits were found for other common ASD-related behaviors, including stereotypies, repetitive behaviors, and oppositional behaviors [8].…”
Section: Introductionmentioning
confidence: 99%